Anti-Soviet Resistance in Kaunas 1946–1947 - Pocius, Mindaugas (Genocidas ir rezistencija, 2011)
The article explores efforts of the leadership of Tauras Command to expand the activities of the partisans and the underground reservists in Kaunas in 1947 as well as the anti-Soviet activities of students of Vytautas Magnus University and the Academy of Agriculture of Lithuanian in 1946–1947. The article attempts to answer the following questions: how did the activities of the partisans of Birutė Special Team (Tauras Command) and the reservists in Kaunas manifest themselves and why were they special? Did the underground leadership plan to destroy the following top officials of the country − the most well-known traitors of the homeland: Antanas Sniečkus, First Secretary of the Communist Party of Lithuania, Mečislovas Gedvilas, Chairman of the Soviet Council of Ministers of Soviet Lithuania, Justas Paleckis, Chairman of the Presidium of the Supreme Council, and others? To sum up the results of the study, it can be stated that in the first few years after the war, various underground youth organisations and groups, whose members were usually young people originally from villages and with strong national identity, were actively involved in anti-Soviet activities in Kaunas higher schools. In May–June 1947, there were four corps (2, 3, 4, and 5) of Birutė Special Team (Tauras Command) Kaunas Group. They mostly consisted of partisans and members of the organisational sector (reservists). Members of these corps carried out armed campaigns, distributed underground press, and collected material assets for the needs of Tauras Command. For geographical strategic reasons, the leadership of Tauras Command planned to establish the Central Command Post of Lithuanian partisans in Kaunas, therefore, they sought to expand its influence in the city. In the first half of 1947, the leadership managed to set up organisational units and begin active underground activities in the city of Kaunas. However, due to the relatively efficient operations of the USSR state security agents, it became complicated for partisans to carry out their actions. In summer-autumn 1947, the Ministry of State Security managed to detain most of the freedom fighters of Birutė Special Team Kaunas Group, as well as the reservists. The alleged assassination attempt of Justas Paleckis, Chairman of the Supreme Council of the LSSR, by the corps of Birutė Special Team Kaunas Group still remains a mystery. A possible version has not been confirmed by other independent sources. On the other hand, it is certain that the leadership of Tauras Command did have a plan to destroy leaders of the LSSR (Sniečkus, Gedvilas, and Paleckis) and encouraged leaders of the corps of Kaunas Group to prepare for the assassination of the highest government officials.